To assess the effect of antiretroviral therapy on HIV/AIDS patients at art plus center Bhopal: a retro respective study - Verma, Hemant; Rathore, Bhavishya; Sharma, Jeetandra; Toppo, Manju (International Journal Of Community Medicine And Public Health, 2016)
Background: To assess the immunological and clinical progress of human immunodeficiency virus/acquired immune deficiency syndrome patients on antiretroviral therapy at antiretroviral therapy (ART) center Bhopal, Madhya Pradesh, India. Methods: Retrospective medical records review was conducted to determine the immunological and clinical progress of HIV/AIDS patients. The records of patients on their clinical stage, cluster of differentiation 4 (CD4) Count, and working status were reviewed. Results: A total number of 5295 patients were included in the study. The mean age was 33.39 Years and standard deviation 11.84 years; it ranged from 0.5 to 82years. Number of males was 3441 (64.98%), females formed 1829 (34.54%), while transgender 25 (0.47%). Out of 5295 patients 3314 (%) are eligible and initiated ART. And out of 3314 patients, 1903 patients continue to be present at their follow up visit for regular clinical and pathological checkup. The mean weight of the patients increased from 49.59kg to 52.41 after 12 months of therapy. Mean CD4 cell counts as 231cells/mm3 during the first follow up increase to 443 cells/mm3 at 2nd visit. Before ART 674 Patients were working and 373 were bedridden and after 1 year of ART 1028 were became belongs to working group and only 197 were remains bedridden. Percentage of patients in stage III became 38.94% (from 48.84%) followed by Stage II 38.36% (from 23.08%). Conclusions: Study concluded that the patients taken ART were shown to experience improved health status in general.